A reinvenção dos micro e pequenos negócios e tempos de pandemia do COVID-19 no município de São Bento do Tocantins-Brasil. - Silva, Natália Araújo da (Universidade Federal do Tocantins, 2023)
The work presented here is an article whose main scope is theoretical and practical research on the reinvention of micro and small businesses in times of the Covid-19 pandemic in the municipality of São Bento do Tocantins - Brazil. With the theme, The reinvention of micro and small businesses in times of the covid-19 pandemic in the municipality of São Bento do Tocantins-Brasil, its general objective is to analyze the innovations developed by traders to overcome the Covid-19 pandemic in the municipality of São Paulo. Sao Bento do Tocantins. Its specific objectives are initially proposed to identify the innovations created by micro and small businesses to overcome the pandemic crisis and later seek to relate the actors involved in overcoming the covid-19 crisis in the municipality. In this way, your research problem seeks to answer the following question: How to overcome the challenges imposed by the market in times of a pandemic? The present work has as its central theme, the reinvention of micro and small businesses in times of the Covid-19 pandemic in the municipality of São Bento do Tocantins. With the following topics, in the theoretical framework: reflections of the pandemic process on micro and small businesses and e-commerce in Brazil and its transformations. In the results and discussions, it presents an interview with two local companies, with questions and answers about the pandemic period. Given the above, it is clear that there was something positive after the scenario in which traders faced, succeeded and reinvented themselves.